Differentiation theory : intersensory substitution and the use of the sonicguide - Aitken, Stuart (The University of Edinburgh, 1981)
This thesis investigates the possibilities and parameters of intersensory substitution - the provision through one sense of information normally provided through another sense. An artificial ultrasonic echo-location device, providing, through sound, information usually provided through sight, was used. A series of interlinked cross-sectional and longitudinal studies was run, using both blind and simulated blind subjects of a range of ages. Infants, pre-school children, school-age children and adults were tested. Although some subjects in all age groups were shown to be able to make some use of the device, by adopting strict criteria for testing the effectiveness of this use, both qualitative and quantitative age differences in use were demonstrated to exist. The implications of these results for conflicting theories of development, in particular perceptual development, are considered. A differentiation theory in which development is seen as proceeding from abstract to specific, while not consistent with all the results, is shown with modification, to have the greatest explanatory value.